Coronary microvascular dysfunction is associated with reduced cardiac performance in low flow low gradient aortic stenosis. (3rd October 2022) - Scarsini, R; Pighi, M; Mainardi, A; Portolan, L; Mammone, C; Benfari, G; Springhetti, P; Fanti, D; Bergamini, C; Tavella, D; Pesarini, G; Ribichini, F L
Abstract: Background: Little is known about coronary microvascular function of patients with low-flow low-gradient aortic stenosis (LFLGAS). We hypothesized that LFLGAS is associated with more severe coronary microvascular dysfunction (CMD) compared with normal-flow high-gradient aortic stenosis (NFHGAS) and that CMD is related to reduced cardiac efficiency. Purpose: To perform a prospective invasive assessment of CMD in patients with LFLGAS undergoing TAVI and to compare it with patients with NFHGAS. Moreover, we aimed to assess the possible acute impact of TAVI on coronary microvascular function and the interactions between CMD and of cardiac performance at speckle tracking echocardiography (STE). Methods: Invasive thermodilution-based assessment was systematically performed in 41 consecutive patients with isolated severe AS with angiographic unobstructed coronary arteries undergoing TAVI. The index of microcirculatory resistance (IMR), resistive reserve ratio (RRR) and coronary flow reserve (CFR) were derived to assess coronary microcirculatory function before and after TAVI. Advanced echocardiographic imaging, including STE, was performed to assess cardiac function. Results: IMR was significantly higher in patients with LFLGAS compared with patients with NFHGAS (24.1 [14.6–39.1] vs 12.8 [8.6–19.2] p=0.002). Similarly, RRR was significantly lower in LFLGAS compared with NFHGAS (1.4 [1.1–2.1] vs 2.6 [1.5–3.3] p=0.020). No significant differences were observed in CFR between the two groups. High IMR was associated with low stroke volume index (rho=−0.427, p=0.005), low cardiac output (rho=−0.517, p=0.001), reduced peak atrial longitudinal strain (PALS) (rho=−0.610, p≤0.001) and presence of atrial fibrillation (54.6% vs 21.1%, p=0.036). Conversely, IMR was only modestly associated with the mean pressure aortic valve gradient (rho=−0.304, p=0.054). Notably, the mean gradient was significantly associated with IMR in the NFHGAS group (rho=0.632, p=0.003) but not in the LFLGAS (rho=−0.222, p=0.333). Similarly, high IMR was associated with the AVA in the NFHGAS group (rho=−0.50, p=0.025) but not in patients with LFLGAS (rho=0.157, p=0.497). Paradoxical LFLGAS emerged as a phenotype associated with CMD, poor left ventricular longitudinal systolic function and left atrial dysfunction. TAVI determined no significant variation in microvascular function (IMR: 16.0 [10.4–26.1] vs 16.6 [10.2–25.6], p=0.403) and in PALS (15.9 [9.9–26.5] vs 20.1 [12.3–26.7], p=0.222). Conversely, left ventricular global longitudinal strain increased overall after TAVI (−13.2 [8.4–16.6] vs −15.1 [9.4–17.8], p=0.047). Conclusions: LFLGAS is associated with impaired coronary microvascular function compared with NFHGAS. Combined invasive assessment of microvascular function and advanced non-invasive imaging contributed to define different AS phenotypes. CMD was associated with low-flow state, left atrial dysfunction and reduced cardiac efficiency in patients with AS. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott Vascular